Korelasi Pengetahuan Ekofeminisme dengan Keterlibatan Konsumen pada Gerakan Sustainable Beauty Sociolla Kota Banjarmasin - Ariani, Siti Noor; Hamid, Ismar (Prodi Sosiologi FISIP ULM, 2024)
The beauty industry is experiencing significant growth, leading to the potential for substantial environmental impact. Thus, changes in human behavior are key to addressing the environmental crisis. This research aims to determine the correlation between ecofeminism knowledge and consumer involvement in the Sociolla sustainable beauty movement in Banjarmasin. There are two hypotheses in this study: Hypothesis (1) Beauty product consumers understand ecofeminism ethics. Hypothesis (2) There is a relationship between ecofeminism ethics and the Sustainable Beauty Movement. This study uses a quantitative method with purposive sampling, involving 50 respondents. Data were collected using the ecofeminism ethics scale (consisting of 13 valid items, with α = 0.952) and the sustainable beauty movement scale (consisting of 14 valid items, with α = 0.865). The data analysis techniques employed include descriptive statistics, simple regression, and correlation. The results show a positive and moderately strong relationship between ecofeminism ethics and the sustainable beauty movement (r = 0.502). The more consumers understand ecofeminism ethics, the stronger their behavior supports environmental sustainability. The contribution of ecofeminism ethics to the sustainable beauty movement is 36.2%, with the remainder contributed by other factors. The conclusion of this study is that the first hypothesis (H₁) stating that women have an understanding of ecofeminism is accepted. Furthermore, the second hypothesis (H₂) stating that there is a relationship between ecofeminism ethics and the sustainable beauty movement, including the use of recycle stations among beauty product consumers, is accepted. Continuous use of beauty products by consumers can increase waste from used beauty products. Recycle stations aim to reduce environmental impact, and it is hoped that consumers who have not yet participated will join in realizing environmental sustainability, especially in the beauty industry.